2u-9=u-8

Simple and best practice solution for 2u-9=u-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u-9=u-8 equation:


Simplifying
2u + -9 = u + -8
Reorder the terms:
-9 + 2u = u + -8
Reorder the terms:
-9 + 2u = -8 + u
Solving
-9 + 2u = -8 + u
Solving for variable 'u'.
Move all terms containing u to the left, all other terms to the right.
Add '-1u' to each side of the equation.
-9 + 2u + -1u = -8 + u + -1u
Combine like terms: 2u + -1u = 1u
-9 + 1u = -8 + u + -1u
Combine like terms: u + -1u = 0
-9 + 1u = -8 + 0
-9 + 1u = -8
Add '9' to each side of the equation.
-9 + 9 + 1u = -8 + 9
Combine like terms: -9 + 9 = 0
0 + 1u = -8 + 9
1u = -8 + 9
Combine like terms: -8 + 9 = 1
1u = 1
Divide each side by '1'.
u = 1
Simplifying
u = 1

You can always share this solution

See similar equations:

| 2x^2-2(x-2)=20 | | (4u-7)-(-13u+8)= | | 3(d+3)=15 | | 3x+3=9x | | 2.5h-15=4j | | 3y-7=-2 | | 6x+35+x=15(x+4)-25 | | 2(a-6)=36 | | -4.2=1.7+x | | 0.4x-0.3y=1.4 | | 4.2=1.7+x | | -0.2x-0.3=0.2 | | x^2+4kx+5k=0 | | 3(x+5)+x=-7 | | 2f+4=9 | | -18+8x=5x+36 | | 5n+3n+7=15 | | 2(9x-50)=3-3(x+8) | | 8x-82=107+x | | c+8=2(c+2) | | -3.5=2.7+x | | .6a-.2a-3=17+.08a | | 6+17x-2=9x+94-2x | | 3.3+3.5=5(x-1)+3x | | 12x+16=5x | | 5x-3(x-2)=26 | | 5a-4=11 | | z=4x+5y | | 9x-38=6x+22 | | 4n-7= | | 73+11-5m-2=2m-9 | | -7x+2=75 | | (x+2)+(9x-22)=180 | | -7x-2=75 | | 2x+3x-4+5x+14+10x+4=1080 | | 17x-8=3+16 | | (2x-28)=(x+3) | | 4x-2=6x-46 | | X+4.7=8.1 | | 2+-1ln+3lnx=0 | | y+3=1(x-1) | | (8x+1)+(2x+9)=90 | | 4(x-1.1)=8.8 | | 6x-67=141-10x | | 7x^2+53x+8=0 | | z^2+(z+2i)z+3+2i=0 | | y+3=-1x-1 | | (13x-20)=(9x+32) | | y+3=-1-1 | | -4x+24=-48x+8x | | (4x+40)=(8x+8) | | (3+3)(6+8X)=10-3.5(X+1) | | 5X-1.8=-X+2.4 | | z^3-3z^2+6z-4=0 | | m^3+m^2+m+1=0 | | 4(5x+3)=152 | | 2y+3y+8=23 | | 4(5x+12)=152 | | 4+66x=33x+31 | | (4+2x)=8(x+9) | | (x^4-x+y)dx-xdy=0 | | 17x-45+3(3-3x)=2(12x-7)-3(-3x-7) | | 2w+5(5+w)=42 | | -16x+y=52 | | -1+3x=-3x+17x |


Related pages


315.31calculator derivatex1234differentiation of axcosx cos3x642-42711111111 to decimalmz 12xsx equation0.125 fractioncosx secxlcm of 75solve 3x2 12x 154y 6x 2how to enter fractions on a calculatorlcm of 63what is twenty percent of fifty dollarscos3x sin3xlog3x 3get easy solution expression calculator729.2724.5roman numerals 92what is 7x8sin 6x cos 6x3x-5y 933.333 as a fraction84 in roman numeralswrite the prime factorization of 24prime factorization of 360cos 2pi2y 3x 14z rootcos 4x sin 4x cos2xy 3sinxx2 3x 7 098.1 easy9k1118x20.4375 as a fraction25kg lb70-350derivative of lnx xderivative calculator step by step2x 5y 16the prime factorization of 105pv nrt solve for ncosx derivative25kg to lbs2x 6y 12144200derivative of 9xmultiples of 252solve 3x 2y 6130 in roman numeralsquare root of 0.16300-224derivative of tanx 2log2x 3fraction percent to fraction calculatortwo step equations calculator with fractions12.5 percent as a decimalwhat is the prime factorization of 420bx-25 x2finding solutions to equations calculatorgreatest common factor of 120whats prime factorization1iv2x 3y 4zthe derivative of tanx7xy5abcwrite 88 as a product of prime factorsanc calculation equation2x 2 6xadding simple fractions calculatorgreatest factor calculator39.99 usd in gbp